2014
DOI: 10.5658/wood.2014.42.5.615
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbonization Temperature on Hygric Performance of Carbonized Fiberboards

Abstract: Increases of public attention on healthy environment lead to the regulation of indoor air quality such as Clean Healthy House Construction Standard. This standard covers emission of total volatile organic compounds (TVOCs) (e.g., formaldehyde, benzene, and toluene), ventilation, and use of environmentally-friendly products or functional products. Moisture absorption and desorption abilities are a recommended functionality for improving indoor air quality. In this study, moisture absorption and desorption capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In 2009, a crack-and twist-free carbonized board was developed by using medium-density fiberboard (MDF), plywood, and wood panels (Park et al 2009). The physicochemical properties and functionality of carbonized MDF (c-MDF) have been investigated (Zhou et al 2013;Lee et al 2014;Lee et al 2017a,b). The c-MDF can easily remove formaldehyde (a major volatile compound contributing to sick house syndrome) and shows some ability to remove other aromatic volatile organic compounds (VOCs), such as toluene and xylene, from indoor atmospheres (Park et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, a crack-and twist-free carbonized board was developed by using medium-density fiberboard (MDF), plywood, and wood panels (Park et al 2009). The physicochemical properties and functionality of carbonized MDF (c-MDF) have been investigated (Zhou et al 2013;Lee et al 2014;Lee et al 2017a,b). The c-MDF can easily remove formaldehyde (a major volatile compound contributing to sick house syndrome) and shows some ability to remove other aromatic volatile organic compounds (VOCs), such as toluene and xylene, from indoor atmospheres (Park et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The 10 times homogenized loess-treated c-MDF showed lower moisture absorbing and desorbing properties than the other amounts of repeated homogenization, which meant that the loess particle size was reduced to cover all micro and macro pores of c-MDF. Lee et al (2014) explained that not only chemical reactions of materials including wood, wood-based board, and c-MDF influence absorption and desorption, but also physical reactions between materials, which can be influenced by moisture. Furthermore, moisture buffering in porous surfaces was found to have a large influence on the humidity distribution of the dwelling.…”
Section: Morphologymentioning
confidence: 99%
“…The carbonization process does not require any chemical additions, and the cellular anatomical features of the wood are retained in the new carbon material (Treusch et al 2004). In the authors' previous study, carbonized wood-based materials were introduced for use as environmentally friendly indoor construction materials, because they had excellent flame retardant qualities, sound absorption, electrical resistance, and hygric performance (Kwon et al 2013;Lee et al 2014;Park et al 2014). In particular, Lee et al (2014) reported that the moisture absorption and desorption capacity of medium-density fiberboard (MDF) were significantly improved by carbonization, and that the highest value was obtained at 600 °C.…”
Section: Introductionmentioning
confidence: 99%